2021
DOI: 10.1371/journal.pone.0256888
|View full text |Cite
|
Sign up to set email alerts
|

Reduced mood variability is associated with enhanced performance during ultrarunnning

Abstract: Ultrarunning requires extraordinary endurance but the psychological factors involved in successful ultrarunning are not well understood. One widely held view is that fluctuations in mood play a pivotal role in performance during endurance events. However, this view is primarily based on comparisons of mood before and after marathons and shorter running events. Indeed, to date no study has explicitly examined mood changes during a competive ultramarathon. To address this issue, we measured mood fluctuations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…Although our participants were recreational rather than elite triathletes, it is likely that pre-competition anxiety and a preoccupation with thoughts associated with competing and/or completing the event, contributed to increased feelings of tension. Our results are also consistent with the findings of Burgum and Smith (2021) who reported a significant increase in Tension scores immediately prior to racing among ultradistance runners.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although our participants were recreational rather than elite triathletes, it is likely that pre-competition anxiety and a preoccupation with thoughts associated with competing and/or completing the event, contributed to increased feelings of tension. Our results are also consistent with the findings of Burgum and Smith (2021) who reported a significant increase in Tension scores immediately prior to racing among ultradistance runners.…”
Section: Discussionsupporting
confidence: 92%
“…These highly variable factors, each with strong potential to substantially disrupt performance, have great capacity to overshadow the effects of pre-event mood upon performance outcomes, perhaps explaining why mood did not associate with performance in this triathlete sample. A recent study of mood fluctuations during ultrarunning ( Burgum and Smith, 2021 ), which reported significant in-event increases in Anger, Fatigue and TMD scores, both confirmed the potential for in-event mood fluctuations to occur and supported the benefit of mood stability on performance among endurance athletes.…”
Section: Discussionmentioning
confidence: 73%
“…After testing the stress states of nishers in a mountain ultramarathon, it was found that EI had a positive effect on pre-competition and mental preparations [8], concluding that those with higher EI may have more readily adaptable psychological states, which supports a key difference in why some athletes may more effectively adapt and succeed in recovering ultramarathons than others [43]. Because EI correspond with lower TMD, which supports greater performance [9], the greater the EI, the more likely an ultramarathoner is to succeed in their event.…”
Section: Emotional Intelligencementioning
confidence: 99%
“…It is widely believed that mood uctuations in ultrarunning play an important role in performance during an ultramarathon [8, 9,18]. Studies have analyzed mood states in ultrarunning using the Pro le of Mood States (POMS) or the Brunel Mood Scale (BRUMS), nding that between one week and one month of running an ultramarathon, substantial mood alterations took place [6].…”
Section: Mood Variabilitymentioning
confidence: 99%
See 1 more Smart Citation